Civil society, social authority and consciousness: the subject for urban regeneration - Zohreh Fanni (Sustainable Earth Trends, 2021)
Today, cities in the world are facing a range of related economic, social and environmental issues and problems. The reason of axial study on the subject of urban regeneration policy by urban researchers and planners in the world is that this program will be unifying and integrating all economic, cultural, social, environmental and physical aspects in urban structure. Urban public spaces and civil society are the mirror of social power, intelligence and development of their people as much as they can make strong social cohesion, health and welfare of the citizens. These spaces bring about human activities' integrity, solidarity of spatial organization of city and social capital production. The main questions of this study are: What is the relationship between civil authority, consciousness and urban regeneration? What factors influence on lack of public authority in the urban regeneration? The results of this study show that process of urban regeneration would be effective stimulus if the city has been built and operated basis on the human reason, consciousness and authority in public realms as civil society. In this case, the city can also be effective to restore and strengthen its neighborhoods. One of the main characteristics of Iranian urban spaces is existence of unfair approach which has caused to descend access of all people to the facilities and equipment of life and activity.